Caribbean in a new international context: are freedom and peace a threat to its prosperity? - Dominguez, Jorge (North South Centre MiamiUS, 1993)
Seeks to answer the question whether the new freedom and peace are a threat to the prosperity of the Caribbean's peoples. Concludes that the Caribbean can respond to the international challenges by continuing, and deepening the economic policies that have been underway in nearly all countries of the region. Suggests that there will be domestic costs in the Caribbean joining NAFTA but the costs of remaining outside NAFTA would be greater.